2021
DOI: 10.1111/ppl.13329
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous salicylic acid alleviates the negative impacts on production components, biomass and gas exchange in tomato plants under water deficit improving redox status and anatomical responses

Abstract: Salicylic acid (SA) is an interesting messenger in plant metabolism that modulates multiple pathways, including the antioxidant defence pathway, and stimulates anatomical structures essential to carbon dioxide fixation during the photosynthetic process. The aim of this research was to determine whether pre-treatment with exogenous SA can alleviate the deleterious effects induced by water deficit on production components, biomass and gas exchange, measuring reactive oxygen species, antioxidant enzymes, variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 106 publications
(122 reference statements)
4
11
2
Order By: Relevance
“…Water reductions at the levels of 40, 30, and 20% of the WHC induced the reduction of vegetative growth of tomato plants, lower shoot heights (SL), leaf area (LA), as well as less biomass accumulation in shoot and roots can be observed. Such changes are expected in tomato plants exposed to drought (Lobato et al 2021;Moles et al 2018;Zhou et al 2017) and can be attributable to lowers photosynthetic rates induced by drought stress (Liang et al 2020), confirmed by reductions in CO 2 assimilation rate (A), stomatal conductance (gs), and leaf transpiration (E) observed in this study and linked positively to growth variables (Fig. 4).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Water reductions at the levels of 40, 30, and 20% of the WHC induced the reduction of vegetative growth of tomato plants, lower shoot heights (SL), leaf area (LA), as well as less biomass accumulation in shoot and roots can be observed. Such changes are expected in tomato plants exposed to drought (Lobato et al 2021;Moles et al 2018;Zhou et al 2017) and can be attributable to lowers photosynthetic rates induced by drought stress (Liang et al 2020), confirmed by reductions in CO 2 assimilation rate (A), stomatal conductance (gs), and leaf transpiration (E) observed in this study and linked positively to growth variables (Fig. 4).…”
Section: Discussionsupporting
confidence: 82%
“…However, 20% WHC reduced this variable. Effects of soil drench with SA (+SA-root) on A, gs, and E were observed in well-watered conditions but not with water-restriction, differing from reports that relate gains in photosynthesis induced by SA under drought (Hayat et al 2008;Lobato et al 2021). Alternatively, results of this work agree with Gharbi et al (2018) who observed that SA positively impacted net photosynthesis, but in unstressed plants only.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations